Non-school activities and their relationship to some variables. “A field study on a sample of learners of the first cycle of basic education in Latakia Governorate”: - غانم ثناء (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The current research aimed to determine the type of activities of the learners of the first cycle recorded outside the school and their relationship to each of the variables (grade, gender, the learner’s level, place of residence, father’s certificate, mother’s certificate, mother’s work, family income). Moreover, whether the learners registered them according to their wishes, in order to infer the extent to which they take into account their tendencies on the one hand and the principles of education democracy on the other hand. The descriptive approach was adopted to achieve the research objectives and data were collected by applying the interview to a sample of 300 learners from Latakia. The results showed that 93.7% register at least one activity and 87% have registered at least an academic activity, and it was found that there is no relationship between the type of activities recorded outside the school and both the grade and the gender of the learner. While it showed a statistically significant relationship between the rest of the variables and the type of activities recorded by learners outside the school, it was found that recreational activities are recorded by the desire of learners, while academic activities are recorded by the desire of parents often.